PENGARUH PROSEDUR PENERJEMAHAN POLA DAN JENIS KALIMAT BAHASA INDONESIA DAN INGGRIS DALAM NOVEL TERJEMAHAN CALON ARANG: SEBUAH ANALISIS KONTRASTIF - Griselda Felicia Fredyryna Tumbole; Sajarwa Roman (PRASASTI: Journal of Linguistics, 2022)
The purpose of this study was to examine the effect of translation procedures and types of sentences from Indonesian (BSU) into English (BSA) in Indonesian literary novels by Pramoedya Ananta Toer "Candidate Charcoal" and the novel of the translation "The King, The Witch, and the Priest "The translated by Willem Samuels. The object of this research is Indonesian sentence in novels with the type of sentence and sentence patterns that are not common among literals. The contrastive analysis approach is used in this study, and is presented using qualitative descriptive research method. The results showed that the results showed that the results Sentences in BSU and BSA can have different patterns and types of sentences but have the same meaning. Sentences in BSU contain different patterns and types of sentences or can be classified as sentences with typical writing, but when translated into BSA, patterns and the type of BSU sentence is unique into a general pattern and sentence his. Therefore, the influence of transposition translation procedures on the pattern and type of BSU sentence is a decrease in the originality of writing literary literary works in translation literary works.